Bicycle helmets - Are low drag and efficient cooling mutually exclusive? - Fitzgerald, S.; Atkins, H.; Kelso, R.; Dimitriou, A. (Proceedings, 2018)
An aerodynamic study was conducted on eleven high-end `aero-road` helmets with the aim of determining whether a helmet can simultaneously have low drag and efficient cooling. The aerodynamic drag of each helmet was measured using a custom-built cycling manikin at a velocity of 40 km/h with a yaw angle range of 0° to ±25° and at velocities of 50 and 58 km/h at 0° yaw. Thermal testing of the cooling abilities of each helmet was conducted with a custom-built heated mannequin headform, which incorporated 36 thermocouples embedded within its surface. Contour plots of the temperature distributions over the head were created together with images obtained by a thermal camera. The results demonstrate that all the aero-road helmets are generally as cool as each other, however, there can be significant differences in the aerodynamic drag.